(untitled) (JED (Jurnal Etika Demokrasi), 2026)
The urgency of this research arises from persistent legal, social, and political resistance to the establishment of minority religious places of worship in Indonesia, which threatens constitutional guarantees of religious freedom and local social cohesion. This study aims to identify and critically analyse conflict resolution strategies employed in the process of establishing minority houses of worship in Semarang City. Adopting a qualitative, descriptive–analytical design, the research uses semi-structured interviews with minority religious leaders, community representatives, and government officials, complemented by direct observation at contentious sites and systematic document analysis of regulations, policy documents, and media reports. Data were examined using thematic analysis, and validity was enhanced through source and method triangulation. The findings reveal a set of interrelated strategies centred on sustained dialogue forums, multi-stakeholder mediation led by municipal agencies, informal negotiation at the neighbourhood level, and incremental regulatory accommodation, which together reduce escalation and create space for mutually acceptable agreements. Nonetheless, unresolved issues persist, including asymmetric power relations, ambiguous procedural standards, and the vulnerability of local agreements to broader political dynamics. The study concludes that durable conflict resolution requires institutionalised and transparent mechanisms that integrate dialogue, mediation, citizenship education, and predictable, fair licensing procedures. The novelty of this research lies in its fine-grained, context-specific mapping of how these strategies are operationalised locally within Indonesia’s regulatory regime on houses of worship. The article contributes conceptually to scholarship on the governance of religious diversity and offers concrete policy guidance for local governments and civil society actors seeking to manage conflicts around minority places of worship.